Religiosity, Social And Psychological Factors On Purchase Decisions And Consumer Loyalty - Rosnaini Daga; Andi Jenni Indriakati (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study aimed to determine and analyse the factors of religiosity, psychological factors on purchasing decisions, and loyalty. The method used in this study is a quantitative research method in the form of a cross-section. The population in this study are Marketplace users who live in Makassar and have purchased Muslim clothing products, especially in the Shopee application. This study uses a sampling technique with purposive sampling, part of a non-probability sampling technique. The sample obtained from the calculation results amounted to 100 respondents who were deemed sufficient to represent the population. The data analysis technique used in this research is the Structural Equation Model (SEM). The results showed that religiosity and psychological factors directly had a positive and significant effect on purchasing decisions. Meanwhile, social factors have a positive and insignificant impact on buying decisions. Religiosity, Social Factors and Psychological Factors have a positive and significant effect on loyalty. Purchase Decision has a positive and significant impact on Loyalty. Religiosity Social Factors and Psychological Factors through Purchase Decisions have a positive and significant effect on Loyalty. The results of this study can also be used for marketing in motivating consumers to make purchasing decisions. This indicator is the strongest indicator of consumer psychology in deciding the purchase of Muslim clothing and always considers increasing customer loyalty based on religiosity so that customers are committed to continuing to be loyal in purchasing Muslim clothing. And can be a reference for further researchers to develop research instruments used in this study.